PERBANDINGAN PERSEPSI POLA ASUH PADA MAHASISWA GORONTALO DAN SULAWESI UTARA - Zulkarnain Antu; Fendi Ntobuo; Alya Kemala Shopianti Talipi; Elma Tiara Anwar; Elsya Salsabila Lahati; Nazla Septiani Pahrun; Putri Syakirah Wira Ibrahim; Trifani Rifai; Meysi Kiki Lay Barreto Pinto (program studi psikologi, 2026)
Parenting studies in Indonesia often treat culture as a descriptive background rather than an empirically tested context. This study compared university students’ perceptions of authoritarian, authoritative, and permissive parenting across two regional-cultural backgrounds: Gorontalo and North Sulawesi. A cross-sectional quantitative comparative design was employed. Participants were 117 first-year students at Universitas Muhammadiyah Gorontalo, comprising 82 students from Gorontalo and 35 from North Sulawesi, recruited non-probabilistically according to predefined eligibility criteria. Data were collected using an adapted four-point Likert version of the Parental Authority Questionnaire. Item analysis retained 20 of the original 29 items, and the composite score yielded a Cronbach’s alpha of .841. Group comparisons were conducted separately for each parenting dimension using independent-samples t tests, supplemented by Hedges’ g effect sizes. No evidence of group differences emerged for authoritarian parenting, t(115) = −0.189, p = .850, g = −0.038; authoritative parenting, t(115) = −1.652, p = .101, g = −0.331; or permissive parenting, t(115) = −1.146, p = .254, g = −0.230. When scores were standardized by the number of items, authoritative parenting had the highest mean endorsement in both groups. These findings indicate converging perceptions of parenting within this university sample, but they do not establish cultural equivalence. Unequal group sizes, the use of regional origin as a proxy for culture, and the absence of measurement-invariance testing limit the interpretation and generalizability of the results. Future studies should employ multisite sampling, assess cultural identification directly, and establish construct comparability before testing mean differences.